Самоменеджмент: процесуальна та диспозиційна характеристика - Штепа, О. (Соціогуманітарні проблеми людини, 2010)
Описано напрями самоменеджменту. За допомогою аналізу наукової структури феномену обґрунтовано, що самоменеджмент є саме технологією самоорганізування. На теоретичному рівні виявлено особливості самоменеджменту у формах поведінки – волі та долаючої поведінки. Наведено результати порівняння самоменеджменту та дескрипторів самоорганізування. Емпірично визначено позиціонування самоменеджменту в координатах "активність" – "оптимізм". Подано авторську Шкалу самооцінки самоменеджменту. Визначено самоменеджмент як технологію оптимального самоорганізування особистості для досягнення значущої для неї мети. A description of directions of self-management is presented in the article. It is proved self-management to be a technology of self-organizing by means of the analysis of scientifi c structure of a phenomenon. Features of self-management in the fi eld of the forms of behaviour such as will and overcoming behaviour are revealed at the theoretical level. Results of the analysis of self-management and self-organizing characteristics are given. It is empirically determined a self-management arrangement in co-ordinates "Activity" – "Optimism". The author’s Scale of a self-estimation of selfmanagement is presented. A self-management defi nition as a technology of optimal self-organizing of a person for achievement by the person the signifi cant goals is given in the article.